2007
DOI: 10.1210/en.2007-1155
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-17β-Induced Human Neural Progenitor Cell Proliferation Is Mediated by an Estrogen Receptor β-Phosphorylated Extracellularly Regulated Kinase Pathway

Abstract: Estradiol-17beta (E(2)) induces rodent hippocampal neural progenitor cell (NPC) proliferation in vitro, in vivo, and after brain injury. The purpose of the present investigation was to determine whether E(2)-induced proliferation observed in rodent model systems generalized to cells of human neural origin and the signaling pathway by which E(2) promotes mitosis of human NPCs (hNPCs). Results of these analyses indicate that E(2) induced a significant increase in hNPC proliferation in a time- and dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 76 publications
6
43
0
Order By: Relevance
“…Interestingly, the relationship between cell proliferation and estradiol is consistent with the results obtained with human neural progenitor cells, while this is not the case with progesterone. Wang et al (2008) found that E2 can induce human neural progenitor cell proliferation, which is mediated by an estrogen receptor beta-phosphorylated extracellularly regulated kinase pathway. The estrogen receptor is the decisive factor influencing cellular response to estrogen (Cobellis et al, 2002), and it was shown to exist in MSCs (Zhou et al, 2001;Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the relationship between cell proliferation and estradiol is consistent with the results obtained with human neural progenitor cells, while this is not the case with progesterone. Wang et al (2008) found that E2 can induce human neural progenitor cell proliferation, which is mediated by an estrogen receptor beta-phosphorylated extracellularly regulated kinase pathway. The estrogen receptor is the decisive factor influencing cellular response to estrogen (Cobellis et al, 2002), and it was shown to exist in MSCs (Zhou et al, 2001;Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Neuronal differentiation seems to be promoted by testosterone both in vitro and in vivo. The recent area of non-genomic effects of steroid hormones and the intersection with well-known intracellular pathways should provide important information related Increase in percentage of BrdU-labeled mature oligodendrocytes after injury To be determined [81] Rat and human NSC from fetal brain Increase in proliferation L-type voltage-gated calcium channels [83] Newborn rat neural progenitors Increase in proliferation GABAA receptor [84] Allopregnanolone Rat adult SVZ NSC Decrease in BrdU-labeled cells in the OB after intraventricular administration in vivo To be determined [85] Mouse and human pluripotent stem cells Increase in proliferation and neuronal differentiation; decrease in apoptosis To be determined [86] Human developing cerebral cortex NSC Increase in proliferation and neuronal differentiation Glutamate NMDA receptor in proliferative effect [88] Dehydroepiandrosterone Rat hippocampal NSC Increase in neurogenesis in vivo To be determined [89] Mouse ESC Increase in proliferation ER-and MAPKdependent [90] Rat developing striatal and adult SVZ NSC Increase in proliferation and neuronal differentiation ER-dependent [91] Mouse and human cerebrocortical neural precursors Increased proliferation ER and ERK [93,94] Mouse ESC-derived NSC Increase in proliferation of dopamine-comitted cells ER [95] Estradiol Mouse adult SVZ Increase in proliferation in vivo after ischemic insult ER and ER [101] Mouse ESC Increased proliferation AR [102] Androgens Cultured rat developing brain and adult neural precursors Increased proliferation, but antagonized EGF-induced proliferation. In fetal cells, increased neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…ER are expressed in neural precursors from developing CNS: both receptors are present in mouse striatal [91] and human midbrain [92] NSC; other groups have reported a preferential expression of ER in mouse [93] or ER in human [94] cells. Estradiol promotes proliferation of striatal [91] and cortical cells of mouse [93] and human origin [94]; for both rodent and human cortical cells, such proliferative effects involved activation of ERK.…”
Section: Estradiol Effects On Stem Cells Are Generally Mediated By Esmentioning
confidence: 99%
See 1 more Smart Citation
“…Estrogen has anti-inflammatory effects via down regulation of glial activation, attenuation of nuclear factor kappa B activation, prevention of liposaccharide induced proinflammatory response decrease in release of superoxide anion from microglia and hydrogen peroxide production, thus limiting reactive oxygen species (ROS) mediated neuronal death following ischemic insult [176][177][178]. 17 Estradiol has been demonstrated to promote neurogenesis in rat brain, and promotes proliferation of neural progenitor cells in vitro [179][180][181].…”
Section: Estrogen Apoptosis Inflammation and Oxidative Damagementioning
confidence: 99%